A high mucosal blocking score is associated with HIV protection. (1st March 2019) - Girard, Alexandre; Rallón, Norma; Benito, José M.; Jospin, Fabienne; Rodriguez, Carmen; Chanut, Blandine; Benjelloun, Fahd; Del Romero, Jorge; Verrier, Bernard; Lucht, Frédéric; Pin, Jean-Jacques; Genin, Christian; et al.
Abstract : Background: Early steps of HIV infection are mediated by the binding of the envelope to mucosal receptors as α4β7 and the C-type lectins DC-SIGN and langerin. Previously Env-specific B-cell responses have been reported in highly exposed seronegative individuals (HESN). Method: Here, we studied gp120-specific antibodies ability to block HIV interaction with α4β7, DC-SIGN and/or langerinin HESN. New cell-based assays were developed to analyze whether antibodies that can alter gp120 binding to α4β7, DC-SIGN and/or langerin are induced in HESN. A mucosal blocking score (MBS) was defined based on the ability of antibodies to interfere with gp120/α4β7, gp120/DC-SIGN, and gp120/langerin binding. A new MBS was evaluated in a cohort of 86 HESN individuals and compared with HIV + patients or HIV − unexposed healthy individuals. Results: Antibodies reducing gp120 binding to both α4β7 and DC-SIGN were present in HESN serum but also in mucosal secretions, whereas antibodies from HIV + patients facilitated gp120 binding to DC-SIGN. Any correlation was observed between MBS and the capacity of antibodies to neutralize infection of α4β7 + CD4 + T cells with primary isolates. Conclusions: MBS is significantly associated with protection in HESN and might reflect altered HIV spreading to mucosal-associated lymphoid tissues. Abstract : Supplemental Digital Content is available in the text